Update in Women’s Health Cardiovascular Disease - Melissa McNeil (Journal of Women's Health, 2026)
The goal in selecting these recent articles was to help identify literature that may change the clinical practice of women’s health for practitioners in the primary care setting. Articles were identified by reviewing the high-impact medical and women’s health journals, national guidelines, ACP JournalWise, and NEJM Clinician.